A soft Pickering emulsifier made from chitosan and peptides endows stimuli-responsiveness, bioactivity and biocompatibility to emulsion. (1st February 2022) - Meng, Xinyu; Liu, Huan; Dong, Xinyu; Wang, Qiqi; Xia, Yongmei; Hu, Xueyi
Abstract: Polymeric Pickering emulsifiers may bring new insights to emulsion theory and practice due to their soft characters. Herein, a group of soft Pickering emulsifiers, chitosan-casein hydrophobic peptides nanoparticles (CS-CHP NPs) were prepared with a non-covalent anti-solvent procedure. The CS-CHP NPs provided the contact angles of 37.2°-87.4°, stabilizing O/W or W/O emulsions with enhanced thermal stability, endowing the emulsion with pH and CO2 /N2 responsiveness. The emulsifying behavior and mechanism presented by CS-CHP NPs were different from that of ordinary hard Pickering emulsifiers, where the appropriate contact angle was 37.2° instead of 87.4° for stabilizing O/W emulsions. Moreover, the nanoparticles possess antioxidant, antibacterial activities and excellent biocompatibility. DPPH and ABTS scavenging activity of the CS-CHP NPs were >220% of that of CS NPs. The last, the emulsion provided high-efficient encapsulation of curcumin, making the soft Pickering emulsifiers a group candidate for drug delivery in food, cosmetics and pharmaceutical industry. Graphical abstract: Unlabelled Image